2012
DOI: 10.1029/2012ja017691
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the nightside poleward boundary: Sounding rocket and ground‐based observations of auroral electron precipitation in a rayed curtain

Abstract: [1] The Cascades2 auroral sounding rocket provides a case study for comparing multipoint in situ ionospheric observations of a nightside auroral poleward boundary intensification with ground-based optical observations of the same event. Cascades2 was launched northward from Poker Flat Alaska on 20 March 2009 at 11:04 UT. The 13 min flight reached an apogee of 564 km over the northern coast of Alaska. The experiment included a five-payload array of in situ instrumentation, ground cameras at three different poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 60 publications
5
17
1
Order By: Relevance
“…This plasma initially showed a broadband energy distribution, associated with Alfvén wave acceleration, which merged with the existing plasmasheet population and evolved into a more mono-energetic population, generally associated with quasi-static electric potential drops. Similar multi-point observations by sounding rockets at lower altitude showed similar results (Mella et al 2011;Lynch et al 2012). Thus, the implication is that the initial formation of the PBI is driven by Alfvénically accelerated electrons, possibly arising from a reconnection site, which subsequently become quasi-statically accelerated electrons.…”
Section: Drivers/causessupporting
confidence: 68%
“…This plasma initially showed a broadband energy distribution, associated with Alfvén wave acceleration, which merged with the existing plasmasheet population and evolved into a more mono-energetic population, generally associated with quasi-static electric potential drops. Similar multi-point observations by sounding rockets at lower altitude showed similar results (Mella et al 2011;Lynch et al 2012). Thus, the implication is that the initial formation of the PBI is driven by Alfvénically accelerated electrons, possibly arising from a reconnection site, which subsequently become quasi-statically accelerated electrons.…”
Section: Drivers/causessupporting
confidence: 68%
“…Electron data from the Physics of the Auroral Zone Electrons II rocket showed a case of a so-called inverted-V structure with plasma sheet electrons accelerated to an energy of several keV, during which field-aligned bursts of cold electrons with a spread in energy from a few tens of eV up to the inverted-V energy, were seen superimposed [Semeter et al, 2001]. A similar event was observed with instruments on the Auroral Turbulence 2 rocket [Ivchenko et al, 1999], and the Cascades-2 rocket, where Alfvénic processes were found superimposed on a quasi-static acceleration signature [Mella et al, 2011;Lynch et al, 2012]. Time-dispersed field-aligned electron bursts by Alfvén waves have also been seen in an inverted-V structure with instruments on the Reimei satellite [Asamura et al, 2009], where the low-energy populations were found to drive instabilities giving rise to vortical auroral forms.…”
Section: Introductionsupporting
confidence: 54%
“…A similar event was observed with instruments on the Auroral Turbulence 2 rocket [Ivchenko et al, 1999], and the Cascades-2 rocket, where Alfvénic processes were found superimposed on a quasi-static acceleration signature [Mella et al, 2011;Lynch et al, 2012]. Time-dispersed field-aligned electron bursts by Alfvén waves have also been seen in an inverted-V structure with instruments on the Reimei satellite [Asamura et al, 2009], where the low-energy populations were found to drive instabilities giving rise to vortical auroral forms.…”
Section: Introductionmentioning
confidence: 53%
“…Two‐dimensional optical observations show that PBIs can appear as north‐south (N‐S), tilted, east‐west (E‐W) structures, beads/swirls, and patches [ Zesta et al ., ]. Along PBIs, there also exist smaller‐scale ray structures which are associated with Alfvén wave activity [ Lynch et al ., ]. PBIs are generally believed to be related to longitudinally localized regions of enhanced reconnection that extend along the polar cap boundary from the ionosphere to the tail.…”
Section: Introductionmentioning
confidence: 99%